STRUCTURAL AND FUNCTIONAL ORGANIZATION OF THE HUMAN SKELETAL SYSTEM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The skeletal system is a complex anatomical structure that provides support, protection, and mobility for the human body. In addition to serving as a mechanical framework, bones act as reservoirs for minerals, produce hematopoietic cells, and participate in endocrine regulation. Understanding the organization and function of bones, joints, and associated connective tissues is crucial for clinical practice, particularly in orthopedics, traumatology, and sports medicine. This article provides a comprehensive overview of the macro- and microstructural features of the skeletal system and discusses their clinical relevance.